MO628: A Clinical Score for Identifying Non-Diabetic Nephropathy in Patients with Diabetes and Kidney Disease. (3rd May 2022) - Bermejo Garcia, Sheila; Agraz, Irene; Vergara, Ander; Jose Soler Romeo, Maria
Abstract: BACKGROUND AND AIMS: Between 50% and 60% of diabetics with renal involvement have nondiabetic nephropathy (NDN). Renal biopsy is crucial for renal diagnosis that includes diabetic nephropathy (DN), NDN or mixed form. The objective of the current study is to provide a tool in the daily clinical practice through a predictive model of NDN that is clue for the indication of renal biopsy. METHOD: Observational, retrospective and multicenter study was undertaken of the pathological results of kidney biopsies in patients with diabetes from 2002 to 2014. A logistic regression analysis and the probability of presenting NDN was calculated using a punctuation score. RESULTS: The cohort of 832 patients includes 621 men (74.6%), median age 61.7 ± 12.8 years, creatinine 2.8 ± 2.2 mg/dL and proteinuria 2.7 (1.2–5.4)g/24 h. Time of evolution of diabetes was 10.8 ± 8.6 years. 26.6% ( n  = 221) of patients presented diabetic retinopathy, 18.8% ( n  = 156) peripheral vasculopathy and 17.7% ( n  = 147) ischemic heart disease. A total of 288 patients (34.6%) presented microhematuria. A total of 39.5% ( n  = 329) presented DN, 49.6% ( n  = 413) NDN and 10.8% ( n  = 90) mixed forms. In the multivariate analysis, age (OR: 1.03; 1.01–1.04; P < 0.001), absence of microhematuria (OR: 0.6; 0.4–0.86; P = 0.005), absence of diabetic retinopathy (OR: 3.97; 2.7–5.82; P < 0.001) and absence of peripheral vasculopathy (OR: 1.61, 1.03–2.52, P = 0.038) were identified as independent risk factors for NDN. A ROC curve with an area under the curve of 0.724 was obtained. A predictive model obtaining a score (see Figure 1) for each variable and finally a NDN prediction score was performed. In our new score, the number increased as increased the probability of NDN. CONCLUSION: In our study, ∼66% of biopsied patients with diabetes presented NDN. Microhematuria, absence of diabetic retinopathy, absence of peripheral vascular disease and older age were identified as independent risk factors for NDN. We obtained a score that increased as increased the probability of NDN. This could be in a next future a useful tool for renal biopsy indication in patients with diabetes and kidney disease.